The exploitation of the AAA strategies by Finnish multinational companies - Haapoja, Anni (My University, 2010)
The differences, advantages and disadvantages of global, local and glocal strategies have been discussed in the literature of international business for decades without any conclusions regarding the best approach. The AAA strategies are a new conceptual framework for deciding how to react to the differences that arise when a multinational company expands across national boundaries. The Global/Local-dilemma argues whether there are differences between countries and cultures, whereas the AAA strategies acknowledge the differences and seek to find solutions for exploiting them. The AAA strategies consist of three different approaches, namely adaptation, aggregation and arbitrage. These approaches, or combinations of them, provide new possibilities for companies to deal with the differences which exist between markets. Companies can gain competitive advantage by accentuating their local relevance, by overcoming the differences with economies of scale or by exploiting the differences between markets. The CAGE distance framework is also included in order to examine how different dimensions of distance affect the market selection and the usage of the AAA strategies. The study is conducted as a qualitative comparative case study with two large, Finnish multinationals producing daily goods. The idea is to link the AAA strategies to the global, local and glocal theories and to examine whether Finnish companies exploit elements of the AAA strategies in their operations in the Russian market. Adaptation strategy is the most used of the AAA strategies by the case companies in the Russian market. The aggregation strategy is also somewhat used, especially in the back-office operations such as procurement. However, arbitrage and the benefits it offers are not yet fully understood and therefore not exploited. Furthermore, distance is not the only factor affecting the market selection; also the potential the target market possesses has an effect.
Keywords: The AAA strategies; The CAGE distance model; multinational companies; The Global/Local-dilemma; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Kansainvälisen yritystoiminnan koulutusohjelma|